Arquitectura: a Condição do Silêncio - Cláudia Moreira Araújo (2021)
The present dissertation aims to study the condition of silence as component of architectural practice. Starting from the idea that we live in a "noise culture", an investigation was conducted with with a view to understanding the relevance of silence in the field of arts and architecture. Silence is explored not as the absence of sound, but as a poetic quality of space and condition that awakens multisensory reactions. The work is built through a multidisciplinary panorama, where the understanding of silence in the various arts is explored. focus in the study and comparison of three works by contemporary architects distinct: the Bruder Klaus Field Chapel, by Peter Zumthor, the Chapel do Monte, by Álvaro Siza and the Wooden Chapel, by John Pawson.